Stigmalisasi Aktivis Mahasiswi di Perguruan Tinggi Islam - Ramlah (SOSIORELIGIUS, 2023)
The phenomenon of changing the style of the headscarf will always occur because it is influenced by modernization and cultural currents that continue to go on and experience changes. This research is very important to do to add to the knowledge and knowledge of the author and further research, especially in the study of the headscarf as a study of scientific themes. The purpose of this research is to find out the causes of the change in hijab style and what treatment female students get when they experience a change in hijab style, namely the syari'i hijab style which is the current trend. The method used in this study is descriptive qualitative with a sociological approach through in-depth interviews with female students who have experienced a change in the style of the headscarf. The results of the study show that the cause of changes in the style of female hijab is caused by the influence of social media such as TikTok, Instagram, Youtube and social construction, especially the environment and work demands. As for the treatment that female students get when they experience a change in the style of the headscarf, including the form of pressing and satirical questions, it becomes the subject of gossip (discussion). The two forms of treatment were obtained by female students which, based on the results of the research, had an effect on daily life, student activities and even the mental and psychological aspects of the female students concerned.